Management of Unilateral Cleft Lip and Palate using Presurgical Nasoalveolar-Molding - Meidarlina, Ista; Alamsyah, Gian Nur (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2025)
Cleft lip and palate (CLP) is a common congenital defect in craniofacial. The patient with  CLP experiences difficulty in breastfeeding which can affect their nutritional status. The presurgical nasoalveolar molding (PNAM) is a device used to overcome this problem. This case report aims to describe the pre-surgical treatment using PNAM with a Hotz-Kogo modification design.  This case report presented a two-week-old infant who had unilateral CLP. The alar base widened, the pro-labium and columella were shortened on one side and tilted towards the non-cleft side, and the minor segment of the maxilla was hypoplastic and retroposition. This patient experienced difficulty in breastfeeding and will be treated with PNAM with ekstra oral strapping and nasal stent. The PNAM was adjusted regularly. After using PNAM, the patient had a good sucking reflex and was easy to breastfeed, the position of the premaxilla was corrected, and the nasal morphology was more symmetrical before labioplasty. The presurgical PNAM is a device that functions as a feeding aid to help the baby get good nutrition and also as a pre-surgical treatment to reduce the severity of oronasal deformity before surgery.